Teaching medical students how to take a sexual history and discuss sexual health issues - Ng, Chirk Jenn; McCarthy, S.A. (Malaysian Medical Association, 2002)
BACKGROUND: Taking a sexual history and discussing sexual health issues with patients form an important part of a medical consultation. These specific communication skills can be acquired through various teaching methods. OBJECTIVE: This paper describes the communication skill workshops conducted for undergraduate medical students on how to talk to patients about sex. METHODOLOGY: 198 medical students participated in a series of workshops conducted in the University of Malaya in 2001-2002. Pre- and post-workshop evaluations of the programme were carried out to find out the students' difficulties and to assess the usefulness of the workshop. The workshop consisted of a short lecture, role-plays and discussion. RESULTS: Only 34 of the participants had received some informal training during their clinical years. The main barriers encountered were gender and age differences, language and choice of words, patients and doctors feeling shy, and cultural differences. The workshop was felt to be useful (mean score 4.38, maximum 5.0), most students felt comfortable during the workshop (mean score 4.10, maximum 5.0) and there was significant improvement in the "comfort level" when talking to patients about sex after attending the workshop (P < 0.001). CONCLUSION: Gender, language and cultural differences were the main barriers in taking a sexual history and discussing sexual health issues among the medical students. Communication workshop was felt to be a useful and comfortable method of learning these specific.